Coffee Management Intensification Has Changed the Tradition of Coffee Forest Use in Southwest Ethiopia - Zerihun Kebebew (International Journal of Forestry Research)
The coffee production system has changed the notion of a forest common resources pool in southwest Ethiopia. It is weakening the customary right on forest through time. The objective of the study was to explore forest resources use in relation to coffee management intensity in southwest Ethiopia. The effect of coffee management intensification was narrated based on the nature of accessing forest resources, local control system, level of forest dependency, and nontimber forest products usage through time. Qualitative data were collected through an interview and walk-in-the-woods. It is worth mentioning that an age-old customary right is devolved, and a modified forest management arrangement is emerging along with the coffee production system. The result showed that coffee agroforest drives the use of forest resources in southwest Ethiopia. Coffee production is replacing the tradition of forest management for nontimber forest products. Collection of nontimber forest products is overwhelmed with coffee harvesting. Honey production area (i.e., Luggoo) has been changed to coffee plot. Only coffee owners hold the right to access coffee agroforest. Individual decisions are bypassing the social arrangement of forest resources usage. The nature and level of forest dependency have been changed along with the intensification of coffee management. In contrary to what most people believe, the study findings showed that better-off households are more forest dependent compared to poor households due to coffee production. The storyline depicts the need for taking into account coffee agroforest in sustainable forest management. The study suggests to revisit the notion of recognizing traditional forest resource usage brings sustainable forest management.